Influência de unidades de luz mono e poliwave na dureza e grau de conversão de cimentos resinosos fotopolimerizáveis - Borges, Giovanna Chaves Souza (2022)
Objective: To evaluate the chemical and mechanical properties at the margins of light cured resin cements with different photoinitiators, using two light sources (monowave and polywave). Materials and methods: Three types of resin cements were used, with different photoinitiators: camphoroquinone, APS system and Ivocerin. Thirty samples were made and divided into 6 groups (n=5). The resin cement samples were made in the shape of a maxillary central incisor (tooth 11) and photoactivated under a 0.5 mm thick ceramic sheet. A single light curing unit emitting two types of light (mono and polywave) was used, only changing the tip (Radii Xpert, SDI). The tip of the equipment was positioned in the center of the sample, using a specific device. To evaluate the degree of conversion, Raman spectroscopy was performed, and for hardness, Knoop microhardness testing was performed. Both evaluated five regions in the samples: cervical, mesial, buccal (center), distal and incisal. Results: for the degree of conversion there was significant difference only for the type of cement (p<0.001) showing the cement with APS photoinitiator presenting satisfactory results; for hardness there was significant difference for cement type, again the cement with APS system (p<0.001), type of monowave light (p<0.001), vestibular region (p<0.001) and interaction type of cement X type of light (p<0.001). Conclusion: The light source when evaluated between polywave or monowave may not be a determining factor in the results of physical properties of resin cements, since regardless of the light, the results will be satisfactory. The vestibular region presenting the best results, leaves as a warning the need for a greater amount of photopolymerization at the margins of the cementation. The photoinitiator of resin cements in most cases can and should be photoactivated with good quality equipment, but the quantity of light beams will not interfere in negative results in its performance.